Hubungan Dukungan Family Caregiver dengan Tingkat Kecemasan Pasien Kanker yang Menjalani Kemoterapi - Nila Nadiyatul Khumairoh; Ike Wuri Winahyu Sari (MEDIA ILMU KESEHATAN, 2023)
Background: One of the psychological impacts that often arises in cancer patients undergoing chemotherapy is anxiety. Family caregiver support is needed to reduce the incidence of them.Objective: To determine the correlation between family caregiver support and anxiety levels among cancer patients undergoing chemotherapy.Methods: This research was a quantitative study with a cross-sectional approach. Sampling used purposive sampling technique with a total sample of 52 respondents. This research was conducted at a public hospital in Bantul, Yogyakarta in June 2023. The instruments used in this study were the Family Caregiver Support questionnaire and the Hamilton Rating Scale of Anxiety (HARS-A), which have been valid and reliable. Data were analyzed using descriptive statistical and Pearson correlation analysis.Results: The mean of family caregiver support for cancer patients was 40.69±12.26 from a range of 15-60. The mean of anxiety in cancer patients was 27.54±6.19 from a range of 13-42. The results showed that family caregiver support was related to the level of anxiety in cancer patients (p=0.002, r=-0.414). It means that the higher the family caregiver's support, the lower the level of anxiety experienced by cancer patients.Conclusions: Family caregiver support is very helpful in reducing the anxiety level of cancer patients undergoing chemotherapy.